ANALYSIS OF DETERMINANTS FOR DETERMINING FINANCIAL INNOVATION AND ITS IMPACT ON BANKING FINANCIAL PERFORMANCE - Wahyudi Wahyudi; Yoko Tristiarto (Journal of Management and Leadership, 2020)
This study aims to determine the determinants of innovation in the financial sector namely size, age, cooperation with external parties and Training and R & D Expenditure and its impact on financial performance. The sample used is 13 banks that have the largest market capitalization and actively innovate every year for 5 years. While the population is a bank listed on the Indonesia Stock Exchange. The data used is secondary data. and using path analysis. The result of testing jointly the influence of size, age, cooperation with external parties and Training and R & D Expenditure and its impact on financial performance, through the ability of innovation, is equal to 0.364 or 36.4%. While the rest of 63.6% is the influence of other factors outside the independent variable. Testing on the basis of the variables of cooperation with external parties have a significant effect on performance through the ability of innovation. While size, age, and Training and R & D Expenditure does not effect the financial performance through the ability of innovation Keywords : Size, Age, Cooperation, Expenditure for Training, Research Development and Financial Performance